A Chinese literature overview on ultra-weak photon emission as promising technology for studying system-based diagnostics. (April 2016) - He, Min; Sun, Mengmeng; van Wijk, Eduard; van Wietmarschen, Herman; van Wijk, Roeland; Wang, Zhihong; Wang, Mei; Hankemeier, Thomas; van der Greef, Jan
Highlights: This review summarizes the academic history of ultra-weak photon emission (UPE) studies regarding Chinese medicine. Clinical UPE data are related to Chinese medicine-based diagnostics. UPE in combination with metabolomics opens new avenues for personalized medicine, based on Chinese medicine diagnostics. Abstract: To present the possibilities pertaining to linking ultra-weak photon emission (UPE) with Chinese medicine-based diagnostics principles, we conducted a review of Chinese literature regarding UPE with respect to a systems view of diagnostics. Data were summarized from human clinical studies and animal models published from 1979 through 1998. The research fields can be categorized as follows: (1) human physiological states measured using UPE; (2) characteristics of human UPE in relation to various pathological states; and (3) the relationship between diagnosis (e.g., Chinese syndromes) and the dynamics of UPE in animal models. We conclude that UPE has clear potential in terms of understanding the systems view on health and disease as described using Chinese medicine-based diagnostics, particularly from a biochemistry-based regulatory perspective. Linking UPE with metabolomics can further bridge biochemistry-based Western diagnostics with the phenomenology-based Chinese diagnostics, thus opening new avenues for studying systems diagnostics in the early stage of disease, for prevention-based strategies, as well as for systems-based intervention in chronic disease.